2014
DOI: 10.1186/1472-6920-14-125
|View full text |Cite
|
Sign up to set email alerts
|

Promoting physical therapists’ of research evidence to inform clinical practice: part 1 - theoretical foundation, evidence, and description of the PEAK program

Abstract: BackgroundThere is a need for theoretically grounded and evidence-based interventions that enhance the use of research evidence in physical therapist practice. This paper and its companion paper introduce the Physical therapist-driven Education for Actionable Knowledge translation (PEAK) program, an educational program designed to promote physical therapists’ integration of research evidence into clinical decision-making. The pedagogical foundations for the PEAK educational program include Albert Bandura’s soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Some preliminary work has found that small-group work, along with interactive and personal education, tends to be most effective. [25][26][27] Future studies, ideally using a randomized controlled design, should be conducted to identify which training methods are likely to result in improved clinical decisions based on the best available evidence by physical therapists of different ages and at different professional stages and eventually to determine the influence of these training methods on patients' outcomes. Our results also stress that current research on PT treatment of knee osteoarthritis does not reflect clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Some preliminary work has found that small-group work, along with interactive and personal education, tends to be most effective. [25][26][27] Future studies, ideally using a randomized controlled design, should be conducted to identify which training methods are likely to result in improved clinical decisions based on the best available evidence by physical therapists of different ages and at different professional stages and eventually to determine the influence of these training methods on patients' outcomes. Our results also stress that current research on PT treatment of knee osteoarthritis does not reflect clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently reported barrier concerns limited time, thereby constraining the identification and interpretation of research evidence; being able to apply research findings to clinical practice has also been reported [ 9 , 18 ]. Tilson et al [ 19 ], have recently identified other common barriers, including an inability to determine the legitimacy of research findings, insufficient research literature on specific patients’ problems, deficient information regarding retrieval skills and an inability to incorporate patient preferences into decision-making, such results coinciding with those reported by Jette et al [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Physical therapist-driven Education for Actionable Knowledge translation (PEAK) program is an educational program designed to promote physical therapists’ integration of research evidence into clinical decision-making [ 7 ]. A mixed methods analysis reported feasibility of the 6-month program based on therapist-participant focus groups and short term EBP learning outcomes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study to assess feasibility for implementing the PEAK program was conducted from 2010-2011 among physical therapists at the University of Southern California clinical practices. Previous reports describe the program and its theoretical underpinnings [ 7 ] and a mixed-method analysis of immediate post-PEAK outcomes [ 8 ]. The purposes of this manuscript are to report 1) long-term outcomes regarding therapists’ EBP-related attitudes, self-efficacy, knowledge and skills, and self-reported behaviors, and 2) therapists’ adherence to participant-generated, evidence-based behaviors in patient care.…”
Section: Introductionmentioning
confidence: 99%